Some aspects of Leibniz algebra theory - Kirichenko, V.V.; Kurdachenko, L.A.; Pypka, A.A.; Subbotin, I.Ya. (Algebra and Discrete Mathematics, 2017)
One of the key tendencies in the development of Leibniz algebra theory is the search for analogues of the basic results of Lie algebra theory. In this survey, we consider the reverse situation. Here the main attention is paid to the results reflecting the difference of the Leibniz algebras from the Lie algebras.